Em làm thử nhé!
Bài 1: \(A=\left[\frac{a^2}{b-1}+4\left(b-1\right)\right]+\left[\frac{b^2}{a-1}+4\left(a-1\right)\right]-4\left(a+b\right)+8\)
Cauchy vào là ra rồi ạ;)
Bài 2: Em chịu
2) Có: \(\sqrt{ab}\le\frac{a+b}{2}=1\); \(\sqrt{a}+\sqrt{b}=\sqrt{\left(\sqrt{a}+\sqrt{b}\right)^2}\le\sqrt{2\left(a+b\right)}=2\)
\(\frac{a}{\sqrt{b}}+\frac{b}{\sqrt{a}}=\frac{\left(\sqrt{a}\right)^3+\left(\sqrt{b}\right)^3}{\sqrt{ab}}\ge\left(\sqrt{a}\right)^3+\left(\sqrt{b}\right)^3=\frac{a^2}{\sqrt{a}}+\frac{b^2}{\sqrt{b}}\)
\(\ge\frac{\left(a+b\right)^2}{\sqrt{a}+\sqrt{b}}\ge=\frac{2^2}{2}=2\)
Dấu "=" xảy ra \(\Leftrightarrow\)\(a=b=1\)